SUCCOR quality: validation of ESGO quality indicators for surgical treatment of cervical cancer. Issue 10 (3rd October 2022) - Boria, Felix; Chiva, Luis; Chacon, Enrique; Zanagnolo, Vanna; Fagotti, Anna; Kucukmetin, Ali; Mom, Constantijne; Chakalova,, Galina; Shamistan, Aliyev; Malzoni, Mario; Narducci, Fabrice; Arencibia, Octavio; et al.
Abstract : Objective: To evaluate whether compliance with European Society of Gynaecological Oncology (ESGO) surgery quality indicators impacts disease-free survival in patients undergoing radical hysterectomy for cervical cancer. Methods: In this retrospective cohort study, 15 ESGO quality indicators were assessed in the SUCCOR database (patients who underwent radical hysterectomy for International Federation of Gynecology and Obstetrics (FIGO) stage 2009 IB1, FIGO 2018 IB1, and IB2 cervical cancer between January 2013 and December 2014), and the final score ranged between 0 and 16 points. Centers with more than 13 points were classified as high-quality indicator compliance centers. We constructed a weighted cohort using inverse probability weighting to adjust for the variables. We compared disease-free survival and overall survival using Cox proportional hazards regression analysis in the weighted cohort. Results: A total of 838 patients were included in the study. The mean number of quality indicators compliance in this cohort was 13.6 (SD 1.45). A total of 479 (57.2%) patients were operated on at high compliance centers and 359 (42.8%) patients at low compliance centers. High compliance centers performed more open surgeries (58.4% vs 36.7%, p<0.01). Women who were operated on at centers with high compliance with quality indicators had a significantly lower risk of relapse (HR=0.39; 95% CI 0.25 to 0.61; p<0.001). The association was reduced, but remained significant, after further adjustment for conization, surgical approach, and use of manipulator surgery (HR=0.48; 95% CI 0.30 to 0.75; p=0.001) and adjustment for adjuvant therapy (HR=0.47; 95% CI 0.30 to 0.74; p=0.001). Risk of death from disease was significantly lower in women operated on at centers with high adherence to quality indicators (HR=0.43; 95% CI 0.19 to 0.97; p=0.041). However, the association was not significant after adjustment for conization, surgical approach, use of manipulator surgery, and adjuvant therapy. Conclusions: Patients with early cervical cancer who underwent radical hysterectomy in centers with high compliance with ESGO quality indicators had a lower risk of recurrence and death.